The effect of alpha-melanocyte stimulating hormone on endotoxin-induced intestinal injury - (:unkn) unknown (ELSEVIER SCIENCE INC, 2001)
We investigated the effect of alpha-melanocyte stimulating hormone (alpha-MSH) on endotoxin-induced intestinal inflammation and the role of nitric oxide and prostaglandins in this response. alpha-MSH treatment (25 mug/rat, intraperitoneally (i.p.); twice daily) reduced the severity of the lesions macroscopically and microscopically. This protective effect was found to be confined mainly to the distal ileum. These lesions were reversed by pretreatment with the non-selective COX inhibitor indomethacin (10 mg/kg, subcutaneously (s.c.)) but not by the selective COX-2 inhibitor nimesulide Q mg/kg, s.c.), the NO donor sodium nitroprusside (4 mg/kg, i.v.) or the iNOS inhibitor dexamethasone Q mg./kg, i.p.) at macroscopic level and reversed by Indo or Dex at microscopic level. Increased peroxidase activity -index of tissue neutrophil infiltration- in the distal ileum of LPS-treated rats was decreased by alpha-MSH and this effect was reversed by pretreatment with Indo. In conclusion, the neuropeptide alpha-MSH has a beneficial effect on endotoxin-induced distal intestinal lesions by a mechanism which probably involves nitric oxide and COX-1 derived prostaglandins. (C) 2001 Elsevier Science Inc. All rights reserved.
Keywords: endotoxemia; alpha-melanocyte stimulating hormone; neutrophils; prostaglandins; nitric oxide; NITRIC-OXIDE SYNTHASE; RAT; INFLAMMATION; DAMAGE; MSH; INTERLEUKIN-1; RECEPTORS